Creative director as a leader (2019)
The current organizational dynamic in the world places universities in a relevant role to be performed in the society. Hence, the concept of “creativity” is studied from the hierarchical levels to understand the implications of completing creative processes within an organization. The creativity in the universities require management plans, which demand effort from strategic leaders to materialize and make the mission tangible to all involved actors in the organization; thus, facilitating the achievement of financial quality results, impact on entrepreneurial spirit and optimal labor climate. Subsequently, the creativity could become a strategic topic in the institutional development plans for the directors. This article shows the theoretical construction of the research Creative Abilities of Private Universities Directors in Manizales and the Relation with the Organizational Climate.